Antecedents of customer purchase intention towards the Perak Gold Dinar - Peredaryenko, Margarita (Graduate School of Management, Centre for Strategic Continuing Education and Training, International Islamic University Malaysia, 2016)
The main objective of this thesis is to explain customer purchase intention towards Perak Gold Dinar (PGD) through cognitive customer behavioural lenses. The conceptual framework of the study represents an extended Theory of Planned Behaviour (TPB) with the inclusion of objective and subjective consumer product knowledge as exogenous variables. The study adopted a mixed method exploratory design – instrument development model. The findings from the initial qualitative enquiry were used to guide the development of the construct measuring customers' PGD purchase-related beliefs. The measure of the objective product knowledge of the customers was also specifically developed for the purpose of this study. The measures of TPB constructs were adapted from among the existing reliable instruments in the literature. The population under study was identified as all the registered customers of one of the largest nation-wide distributors of Gold products in Malaysia. Therefore, the total list of the registered customers was taken as the sampling frame. The sample of 571 respondents was obtained on the basis of simple random sampling. A link to the online questionnaire form was distributed through email by the distributor's company that agreed to facilitate the study. The full-fledged Structural Equation Modelling (SEM) was adopted as the analytical procedure. The research found that the hypothesized structural model assessing the indirect explanatory strength of PGD purchase-related beliefs as well as objective and subjective product knowledge on customers' purchase intention towards PGD using attitudes, subjective norms and perceived behavioural control as mediators fits the data well. Even though the objective product knowledge did not exert a direct influence on PGD purchase intention it was found to be practically an important point of entry to tap into the formation of the purchase intention of the customers towards PGD. The unexpected negative suppression effect by the objective product knowledge revealed its indispensable role in the interplay of cognitive behavioural dynamics underlying the formation of the purchase intention towards the PGD.